The optimization of effective parameters for electrodeposition of reduced graphene oxide through Taguchi method to evaluate the charge transfer - Moozarm Nia, Pooria; Jenatabadi, Hashem Salarzadeh; Woi, Pei Meng; Abouzari-Lotf, Ebrahim; Alias, Yatimah (Elsevier, 2019)
In the present work, the Taguchi experimental design technique, an effective and elegant tool, is employed to design and optimize a system for improving the quality of the products as well as discovering significant factors and optimize the parameters for electrodeposition of graphene oxide, in order to achieve low charge transfer resistance from the minimum number of experiments. Reduced graphene oxide (rGO) was prepared via electrochemical process. Electrochemical Impedance Spectroscopy was employed to evaluate the effects of variables on charge transfer resistance. Graphene oxide concentration, pH, scan rate and number of cycles were chosen as important effective parameters. Charge transfer resistance was minimized by measuring the signal-to-noise (S/N) ratio of the factors. Analysis of variance (ANOVA) was also employed to monitor the parameter influence and optimize the process. © 2019 Elsevier Ltd